Internationalization and economic performance: The mediating role of eco-innovation. (10th January 2018) - Hojnik, Jana; Ruzzier, Mitja; Manolova, Tatiana S.
Abstract: This study explores the relationship between internationalization and firm economic performance by investigating the mediating effect of eco-innovation. Using data from 151 Slovenian internationalized companies and structural equation modeling, we find that internationalization is significantly and positively associated with firm-level economic performance and that eco-innovation partially mediates this effect. These findings strongly indicate that environmental sustainability and the adoption of eco-innovation cannot be neglected when serving foreign markets. Thus, our study emphasizes the role of eco-innovation and speaks to whether or not eco-innovation should be adopted and integrated in firm-level strategies in order to improve economic performance. Highlights: Adoption of eco-innovation is an effective strategy to improve firm performance. Companies that operate in foreign markets are more likely to adopt eco-innovation. Eco-innovation translates internationalization into improved firm performance.